The applications of biotechnology in animal feeding: A critical overview - ZOIOPOULOS (Π. ΖΩΪΟΠΟΥΛΟΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2017)
An effort is made in this article to present the applications of biotechnology as regards the improvement of nutritive value and the development of novel feeds as well as the production of various types of feed additives. With respect to raw materials, quality upgrading by bio technological means has been attempted through lignocellulose breakdown or protein enrichment. In addition, reference is made to bioproteins and feeds derived from transgenic plants, particularly those resistant to herbicides. In turn, reference is made to aminoacids as products of industrial fermentation. Furthermore, various feed additives, products of biotechnology, such as enzymes, antibiotics, probiotics, but also means for depression of methanogenesis in the forestomachs of ruminants, as well as silage agents, like inoculants and enzymes, are commented upon. In certain cases, reference is made to the issue of efficacy of biotechnology products when used in animal nutrition and the subject of feed safety. Finally, because of the need for licensing these products in order to be circulated, reference is made to the provisions of Community legislation governing the marketing of feeds. The article concludes with some thoughts on the future of the sector of application of biotechnology in the case of animal nutrition.